Designing, manufacturing and testing of a micro combined heat and power (micro-CHP) system - Ebrahimi, Masood; Lahonian, Mansour; Farhadi, Sirwan (Kurdistan Journal of Applied Research, 2017)
In the present paper a micro-CHP is designed, built and tested based on a 5 kW diesel engine that is chosen to recover its water jacketing and exhaust waste energy and convert it into hot water. The hot water may be used as heating source or domestic hot water. Heat recovery for the lube oil, radiation, convection, and conduction to ambient is not used since they all count for only 13% of the inlet fuel energy. The results include the main characteristics in the design section, some pictures of the main components, the temperature of exhaust, water jacketing and tap water at different points of the system. In addition the heat recovery at different engine loads is also given. The experiments and results show that the overall efficiency of the CHP system can reach 60% which means more than 30% increase of efficiency when comparing with the case when only electricity was supposed to be produced by the engine.